Promoting flowering, lateral shoot outgrowth, leaf development, and flower abscission in tobacco plants overexpressing cotton FLOWERING LOCUS T (FT)-like gene GhFT1 - Li, Chao; Zhang, Yannan; Zhang, Kun; Guo, Danli; Cui, Baiming; Wang, Xiyin; Huang, Xianzhong (Frontiers in Plant Science, 2015)
FLOWERING LOCUS T (FT) encodes a mobile signal protein, recognized as major component of florigen, which has a central position in regulating flowering, and also plays important roles in various physiological aspects. A mode is recently emerging for the balance of indeterminate and determinate growth, which is controlled by the ratio of FT-like and TERMINAL FLOWER 1 (TFL1)-like gene activities, and has a strong influence on the floral transition and plant architecture. Orthologs of GhFT1 was previously isolated and characterized from Gossypium hirsutum. We demonstrated that ectopic overexpression of GhFT1 in tobacco, other than promoting flowering, promoted lateral shoot outgrowth at the base, induced more axillary bud at the axillae of rosette leaves, altered leaf morphology, increased chlorophyll content, had higher photosynthesis and caused flowers abscission. Analysis of gene expression suggested that flower identity genes were significantly upregulated in transgenic plants. Further analysis of tobacco FT paralogs indicated that NtFT4, acting as flower inducer, was upregulated, whereas NtFT2 and NtFT3 as flower inhibitors were upregulated in transgenic plants under long-day conditions, but downregulated under short-day conditions. Our data suggested that sufficient level of foreign FT might disturb the balance of the endogenous FT paralogs of inducers and repressors and resulted in altered phenotype in transgenic tobacco, emphasizing the expanding roles of FT in regulating shoot architecture by advancing determine growth. Manipulating the ratio for indeterminate and determinate growth factors throughout FT-like and TFL1-like gene activity holds promise to improve plant architecture and enhance crop yield.